Glioblastoma and bevacizumab in elderly patients: Monocentric study. (June 2021) - Barrascout, Eduardo; Lamuraglia, Michele
Purpose: A retrospective monocentric comparison of progression-free survival, overall survival, clinical benefit and tolerability between elderly (age>70) and non-elderly (age ≤ 70) patients receiving bevacizumab for recurrent glioblastoma. Methods: We analyzed 47 patients with recurrent glioblastoma receiving bevacizumab (10 mg/kg every 14 days) between January 2011 and January 2014. Bevacizumab was introduced for all patients at recurrence after a first-line treatment by temozolomide. Results: Nineteen patients were classified as elderly and 28 patients as non-elderly. No statistically significant difference was detected in the groups in terms of progression-free survival (3.8 vs. 4.1 months, p  > 0.05) and overall survival at relapse (5.5 vs. 6.5 months, p  > 0.05). A significant ( p  = 0.01) improvement of Karnofsky Performance Status Scale was observed in non-elderly patients. Conclusions: Despite the small number of patients in this retrospective study, the efficacy and safety of bevacizumab in recurrent glioblastoma appear similar in elderly and non-elderly patients. However, clinical benefit seemed to be less evident in younger patients. A prospective multicentric study integrating geriatric assessment tools and quality of life metrics would be interesting in this patient population.